THE EFFECT OF PROFITABILITY, COMPANY SIZE, AND INSTITUTIONAL OWNERSHIP ON COMPANY VALUE: (A Study of Technology Industry Companies in the Software & IT Services Sub-Sector Listed on the Indonesia Stock Exchange from 2021 to 2023) - Enggar Nursasi; M. Fariz Shevalian Arden; Munfaqiroh, Siti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
The purpose of this study is to analyze the influence of profitability, company size and institutional ownership on company value. This study uses a quantitative approach with multiple linear regression analysis methods. The population in this study is industrial companies in the technology sector sub-sector software and IT services in 2021-2023, with a sample of 33 using the Purposive Sampling method. The results of this study show that profitability, company size and institutional ownership influence the value of the company.